2021
DOI: 10.1007/s00338-021-02159-x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in susceptibility among three Caribbean coral species and their algal symbionts indicates the threatened staghorn coral, Acropora cervicornis, is particularly susceptible to elevated nutrients and heat stress

Abstract: Coral cover is declining worldwide due to multiple interacting threats. We compared the effects of elevated nutrients and temperature on three Caribbean corals: Acropora cervicornis, Orbicella faveolata, and Siderastrea siderea. Colonies hosting different algal symbionts were exposed to either ambient nutrients (A), elevated NH 4 (N), or elevated NH 4 ? PO 4 (N ? P) at control temperatures (26 °C) for [ 2 months, followed by a 3-week thermal challenge (31.5 °C). A. cervicornis hosted Symbiodinium (S. fitti) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…In a companion study, we found that A. cervicornis is particularly sensitive to the combined effects of elevated nutrients and temperature (Palacio-Castro et al 2021). Here we investigated genotypic variation in sensitivity by comparing the performance (growth, survivorship, and photochemical efficiency), and prokaryotic community (bacteria and archaea) of six A. cervicornis genotypes that are used in coral restoration in South Florida.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In a companion study, we found that A. cervicornis is particularly sensitive to the combined effects of elevated nutrients and temperature (Palacio-Castro et al 2021). Here we investigated genotypic variation in sensitivity by comparing the performance (growth, survivorship, and photochemical efficiency), and prokaryotic community (bacteria and archaea) of six A. cervicornis genotypes that are used in coral restoration in South Florida.…”
Section: Introductionmentioning
confidence: 87%
“…Thirty-nine fragments were sacrificed during the experiment (28 at the end of phase 1, and 11 at the end of phase 3; Fig. 1) for a companion study (Palacio-Castro et al 2021), and their removal was recorded as "censored" events to adjust the survivorship curves. These events account for the incomplete information about the survivorship outcome of the removed fragments since it is unknown if they would die or survive if left longer in the experiment.…”
Section: Coral Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Nutrients have been also reported to increase disease prevalence (Vega Thurber et al 2013), and disrupt corals’ associated microbial communities, altering the cycling of nutrients among the coral host and their symbionts (Rädecker et al 2015) and promoting the proliferation of opportunistic or pathogenic microbes (Vega Thurber et al 2009). However, the effects of nutrient enrichment on corals are not always negative and can vary by coral species (Fox et al 2021; Palacio-Castro et al 2021), nutrient levels (D’Angelo et al 2014; Dobson et al 2021), nutrient source (Burkepile et al 2019), exposure time (Fabricius 2005), and the ratio of nitrogen to phosphorus availability (Ferrier-Pagès et al 2000; Rosset et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Corals with these thermotolerant algae are more likely to survive heat stress events (e.g. [23,24]; but see [25]); however, these thermotolerant algae often provide less photosynthate to their hosts under ambient conditions, limiting host growth (e.g. [26][27][28][29][30][31]; but see [32,33]).…”
Section: Introductionmentioning
confidence: 99%